2020
DOI: 10.1302/2046-3758.99.bjr-2020-0128.r1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effect of tibial slope on the stability of medial unicompartmental knee arthroplasty in posterior cruciate ligament-deficient knees

Abstract: Aims Unicompartmental knee arthroplasty (UKA) has become a popular method of treating knee localized osteoarthritis (OA). Additionally, the posterior cruciate ligament (PCL) is essential to maintaining the physiological kinematics and functions of the knee joint. Considering these factors, the purpose of this study was to investigate the biomechanical effects on PCL-deficient knees in medial UKA. Methods Computational simulations of five subject-specific models were performed for intact and PCL-deficient UKA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Furthermore, our previous study indicated that the PCL is crucial to restraining AP translation, by showing a significant difference in the amount of translation between the PCL deficiency and the intact knee in UKA. 15 Defrate et al 37 demonstrated that ACL deficiency alters AP translation, and the difference between the translation of the ACL-deficient knee and the intact knee was more pronounced near full extension. In particular, the ACL has the functionally important role of restricting anterior tibial translations in the medial UKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our previous study indicated that the PCL is crucial to restraining AP translation, by showing a significant difference in the amount of translation between the PCL deficiency and the intact knee in UKA. 15 Defrate et al 37 demonstrated that ACL deficiency alters AP translation, and the difference between the translation of the ACL-deficient knee and the intact knee was more pronounced near full extension. In particular, the ACL has the functionally important role of restricting anterior tibial translations in the medial UKA.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In addition to performing these evaluations, we researched the effects of posterior tibial slope in posterior cruciate ligament (PCL)-deficient patients in a previous study. 15 However, no studies have compared the effects in ACL-deficient and PCL-deficient knee models.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers concluded that a fixed-bearing UKA with a 5–8° posterior tibial slope adjustment can partially compensate for the lack of ACL function and can be a feasible treatment option for ACLD patients. Furthermore, it can maintain a higher average survival period in their study [ 32 34 ]. These findings also explain why the contact structure stress in the knee joint does not show significant changes when the ACL is missing but the other knee ligaments are intact under rotational loads.…”
Section: Disscusionmentioning
confidence: 99%
“…Given the growing awareness of the importance of bony morphology in reconstructive knee surgery and total knee arthroplasty (TKA), many efforts have been made in recent years to increase the knowledge of the role of PTS. 2,5,6 In the case of the PTS, similar to the question of alignment in TKA, it is absolutely necessary to take a step back and first define the goal and insist on uniform reporting. We are still unclear what the real "true PTS" is.…”
Section: See Related Article On Page 243mentioning
confidence: 99%